THE EFFECT OF TALKING STICK TECHNIQUE ON STUDENTS’ SPEAKING ABILITY - Nurdiana; Zelly Putriani; Afrizal; Salsabila Zahra (Journal of English and Arabic Language Teaching, 2026)
This study aimed to determine the effect of using the Talking Stick technique on the speaking ability of the eighth-grade students at SMPN 9 Pekanbaru. The researcher used a quantitative method with a quasi-experimental research design in this study. The population of this study was the eighth-grade students which had the total was 348 students. The researcher used convenience sampling to obtain samples. The sample in this study was 77 students from two classes: 37 students in the experimental class (VIII.5) and 40 students in the control class (VIII.8). In collecting the data, the researcher used an oral test as a pre-test and post-test to determine students' speaking ability. The data analysis technique was the T-test using the SPSS 23 version. The researcher found that sig. (2-tailed) was 0.000. It can be stated that 0.000.